Models of English Songs Textbook in Primary and Junior High School Students - Rahman, Abdul (Linguistik : Jurnal Bahasa dan Sastra, 2016)
Language as system of meaning is unique based on text and context, especially children’s song. Children’s song must be created funny by simple structure and simple language development. In fact, in children’s song textbook in English is found inappropriate development of ideas. However, the text such children’s song is affected by social context to create and to comprehend the message.The objective of this study is to identify how are the development of ideas structures of the songs, to describe what type of development of idea is dominantly used in children’s song textbook both primary and junior high school English textbook. This study is based on descriptive and qualitative designs which focus on the naturalistic of the data. The analysis is conducted by describing the data. There are 4 (four) songs for each school textbook as the data source.The data analysis reveals that development of ideas such the uses of simple sentences, words, clauses and phrases are dominantly used. They imply that children’s songs convey the most interesting information to attract the listeners in written by simple structure, the choice of the pattern is influenced by the development of the ideas and the information is simple and easier to get the message.